Impact of antifibrotic therapy on disease progression, all-cause mortality, and risk of acute exacerbation in non-IPF fibrosing interstitial lung diseases: evidence from a meta-analysis of randomized controlled trials and prospective controlled studies - De-yu Li; Xin Liu; Jing-yi Huang; Wen-lu Hang; Gu-ran Yu; Yong Xu (Therapeutic Advances in Respiratory Disease, 2024)
Background: Nintedanib and pirfenidone are preferred pharmacological therapies for patients with idiopathic pulmonary fibrosis (IPF). However, evidence favoring antifibrotic therapy in patients with non-IPF fibrosing interstitial lung diseases (ILD) is limited. Objective: To investigate the effects of antifibrotic therapy on disease progression, all-cause mortality, and acute exacerbation (AE) risk in patients with non-IPF fibrosing ILDs. Design: Meta-analysis. Data sources and methods: Electronic databases were searched for articles published before 28 February 2023. Studies that evaluated the efficacy of antifibrotic agents in patients with fibrosing ILDs were selected. The primary outcome was the disease progression risk, and the secondary outcomes included all-cause mortality and AE risk. The GRADE criteria were used for the certainty of evidence assessment. Results: Nine studies with 1990 participants were included. Antifibrotic therapy reduced the rate of patients with disease progression (five trials with 1741 subjects; relative risk (RR), 0.56; 95% CI, 0.42–0.75; p  < 0.0001; I 2  = 0; high-certainty evidence). Antifibrotic therapy did not significantly decrease all-cause mortality (nine trials with 1990 subjects; RR, 0.76; 95% CI, 0.55–1.03; p  = 0.08; I 2  = 0; low-certainty evidence). However, in patients with progressive fibrosing ILDs (PF-ILD), antifibrotic therapy decreased all-cause mortality (four trials with 1100 subjects; RR, 0.69; 95% CI, 0.48–0.98; p  = 0.04; I 2  = 0; low-certainty evidence). Conclusion: Our study supports the use of antifibrotic agents in patients with PF-ILDs, which could slow disease progression and decrease all-cause mortality. Trial registration: This study protocol was registered with PROSPERO (registration number: CRD42023411272).